Лінгвопрагматичні засоби актуалізації проблеми фемінізму у романі Маргарет Дреббл «Жорна» - Шаповалова, Ірина Валентинівна; Shapovalova, I. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
На матеріалі англомовного роману Маргарет Дреббл «Жорна» проаналізовано лінгвальні засоби з прагматичною настановою актуалізації проблеми другої хвилі фемінізму. Розглядаючи текст як частину соціального процесу, звернено увагу на умови його творення, а саме соціально-історичні обставини 60-х років ХХ ст. Висвітлення тем сексуального життя, незаконнонароджених дітей та аборту, що вважалося табу у той період, а також використання певних лексичних та стилістичних засобів, таких як лексичні повтори, порівняння, метафори, алюзії та цитати, реалізують імпліцитно виражену комунікативну мету тексту – підвищувати соціальну роль жінок та сприяти лібералізації суспільства. The article is devoted to the analysis of linguopragmatic means employed by Margaret Drabble in her novel The Millstone to explore the problems concerning feminism in the 1960s. The choice of the topic has been influenced by the fact that the linguistic aspect of feministic texts of the given period is not researched so far. Approaching the text as a product of the society at a certain period of time with its sociocultural characteristics, an attempt to determine the peculiarities of the novel as an example of feminist writing has been made. The major lexical and stylistic means expressing the implicit content of the text have been singled out. It is suggested that lexical repetition, metaphor, simile, allusion and citation have high communicative value and assist in the interpretation of the problems raised in the text. Тhe author manages to convey the complexity of the inner world of the woman who is transformed by motherhood. Margaret Drabble employs different linguistic and stylistic means to interact with the readers, to show important information in the text, to make it more expressive, creating a timeless novel about a woman’s destiny.
Linguopragmatic Means of Actualizing the Problems of Feminism in Margaret Drabble’s Novel The Millstone
Keywords: лінгвопрагматика; linguopragmatics; фемінізм; feminism; актуалізація; actualization